2006
DOI: 10.1002/erv.761
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders and attachment: the effects of hidden family processes on eating disorders

Abstract: Aim: This study examined pattern of attachment in cohort of women with an eating disorder to determine what types of selfprotective strategies they used, and further whether there was a specific relationship between strategy and diagnosis. Method: The participants were 62 young women with an eating disorder (19 with anorexia nervosa, 26 with bulimia nervosa and 17 with bulimic anorexia). Attachment was assessed using the Adult attachment interview (AAI), classified using Crittenden's Dynamic-Maturational Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
1
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(150 citation statements)
references
References 22 publications
11
129
1
9
Order By: Relevance
“…Among other factors, bulimic symptoms and body dissatisfaction are related to attachment insecurity accompanied by ambivalent or fearful relationships (Elgin & Pritchard 2006;Ringer & Crittenden, 2007). In cases of bulimia, preoccupied attachment may be predominant, while in anorexia dismissive attachment may predominate (Ringer & Crittenden, 2007;Zachrisson & Skå rderud, 2010). However, specific relationships between attachment patterns and subgroups of eating symptomology are inconsistent (Gander et al, 2015).…”
Section: Attachment and Eating Disordersmentioning
confidence: 99%
“…Among other factors, bulimic symptoms and body dissatisfaction are related to attachment insecurity accompanied by ambivalent or fearful relationships (Elgin & Pritchard 2006;Ringer & Crittenden, 2007). In cases of bulimia, preoccupied attachment may be predominant, while in anorexia dismissive attachment may predominate (Ringer & Crittenden, 2007;Zachrisson & Skå rderud, 2010). However, specific relationships between attachment patterns and subgroups of eating symptomology are inconsistent (Gander et al, 2015).…”
Section: Attachment and Eating Disordersmentioning
confidence: 99%
“…Attachment functioning can be insecure in all types of eating disorder (Ward et al, 2010); however the predominant pattern in anorexia nervosa is dismissive attachment whilst in bulimia nervosa preoccupied adult attachment is the predominant pattern (Elgin & Pritchard, 2006;Ringer & Crittenden, 2007;Zachrisson & Skårderud, 2010). Bulimic patients often have ambivalent relationships characterized by anger, distrust, fear of losing the object and a strong wish for approval (Becker, Belle, & Bellington, 1987).…”
Section: Attachment and Eating Disordersmentioning
confidence: 99%
“…Despite this, the study confirms the risks of parental psychiatric illness for bulimia nervosa. Ringer and Crittenden (2007) examined patterns of attachment in a cohort of 62 women with EDs. They found that most of their sample was struggling with attachment figures and that parents' history and relationship problems were causal factors in the development of an ED.…”
Section: Psychological and Familialmentioning
confidence: 99%
“…The sought after goal in child development, is to achieve adequate harmony between the mother and child in order to enable the child to become autonomous and achieve separation (Ringer & Crittenden 2007). Part of the aetiology of an eating disorder lies in low self-esteem, lack of autonomy, dependence and a failure to separate and become an independent person (Garner 2002).…”
Section: Separationmentioning
confidence: 99%
See 1 more Smart Citation